2021
DOI: 10.1108/lht-09-2020-0241
|View full text |Cite
|
Sign up to set email alerts
|

How social media fosters the elders' COVID-19 preventive behaviors: perspectives of information value and perceived threat

Abstract: PurposeAlthough crisis communication via social media has engaged academia's attention during the disease outbreak, information value for preventive behaviors is inadequately studied. The purpose of this paper is to cast light on how to strengthen the uptake of older people's coronavirus disease 2019 (COVID-19) behavioral outcomes due to information value and perceived threat through social media.Design/methodology/approachThis study designs a survey and applies structural equation modeling to examine a resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(78 citation statements)
references
References 49 publications
(97 reference statements)
5
69
0
Order By: Relevance
“…The extant literature on health behavior indicates the predictive role of perceived health risk on behavior change toward illness prevention and health protection (e.g. Abdelrahman, 2020; Nguyen and Le, 2021; Van der Pligt, 1996). For example, in the food consumption context, Hsu et al (2016) pointed out that food safety concern measures consumers’ anxiety about the quality of food and its effects on health, which positively influences the willingness to buy organic food.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…The extant literature on health behavior indicates the predictive role of perceived health risk on behavior change toward illness prevention and health protection (e.g. Abdelrahman, 2020; Nguyen and Le, 2021; Van der Pligt, 1996). For example, in the food consumption context, Hsu et al (2016) pointed out that food safety concern measures consumers’ anxiety about the quality of food and its effects on health, which positively influences the willingness to buy organic food.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…news articles, poets, songs, videos, infographics) (Pollack et al , 2020). Empirical studies in Vietnam also confirm the role of public health risk communication in raising risk perceptions of the community, thereby determining their COVID-19 preventive behaviors (Nguyen and Le, 2021; Tam et al , 2021). The risk communication work during the COVID-19 pandemic can raise public risk perceptions of COVID-19 and minimize inappropriate behaviors (e.g.…”
Section: Introductionmentioning
confidence: 76%
“…First, the relatively small sample size may yield some statistical concerns. Second, it does not cover characteristics of risk communication messages, including information content, information relevance and source credibility (Nguyen and Le, 2021). Also, it does not include their perception of the efficacy of the public health safety measures, which may be a good predictor of their adoption of preventive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional survey (Naveed et al , 2021) showed the prevalence of conspiracy beliefs and fear of COVID-19 among Pakistan university students and how their conspiracy beliefs could predict their fear of COVID-19. Nguyen and Le (2021) investigated how to strengthen the uptake of older people's COVID-19 behavioural outcomes due to information value and perceived threat through social media, which presented plausible reasons for behavioural disclosure, including facemask wearing, handwashing and social distancing. Li et al (2021) selected the enumeration data of the early COVID-19 theme papers spread on social media networks as the research object and explored the law and characteristics of the spread of scientific papers on social media platforms.…”
Section: Public Perception Of Covid-19 Vaccination and Social Distancingmentioning
confidence: 99%